Service quality analysis and its implications – A study on tourism services in Kodaikannal (International Journal of Scientific Research and Management (IJSRM), 2014)
Tourism is one of the top and fastest growing sectors in the world; it plays a very important role in the economy and stimulated the growth of other dependents This study aims to assess tourist perceptions towards quality tourism services provided by the Management of Kodaikannal by examining the influence of quality tourism product on overall tourist satisfaction at Kodaikannal. In this study, five dimensions of SERVQUAL model were concentrated i.e. Tangibles, Reliability, Responsiveness, Assurance and Empathy. The empirical data were collected from tourists via a survey that yielded 150 usable questionnaires. The data were analysed using a series of multiple regressions to determine the influence of service quality on tourist satisfaction. The findings confirmed that service quality directly influenced tourist satisfaction throughout destination facilities, destination accessibility and destination attraction. As a result, the researcher came to a conclusion that there is a significant influence of the service quality on satisfaction of tourists, and therefore service quality plays an important role in tourism by increasing the level of tourist satisfaction. The results in this study supported the evidence that there are positive implications of components of tourism product on satisfaction of tourists.